2023
DOI: 10.3389/fimmu.2022.1023213
|View full text |Cite
|
Sign up to set email alerts
|

Updates on immunological mechanistic insights and targeting of the oral lichen planus microenvironment

Abstract: Oral lichen planus (OLP) is a chronic immune inflammatory disease that is an oral potentially malignant disorder (OPMD), occurs in the oral mucosa and affects approximately 0.5% to 4% of the general population. There are usually five types of OLP: reticular/papular, plaque-like, atrophic/erythematous, erosive/ulcerative, and bullous. Furthermore, the chance of causing oral squamous cell carcinoma (OSCC) is 1.4%. Although the etiology of OLP is still unknown, accumulating evidence supports that immune dysregula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 141 publications
0
22
0
Order By: Relevance
“…promote the pathological progression of OLP. [39][40][41] At present, glucocorticoids, as the first-line anti-inflammatory and immunosuppression drug, were used in clinical OLP treatment. Although glucocorticoids provided an extent of symptomatic relief, they were prone to side effects and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…promote the pathological progression of OLP. [39][40][41] At present, glucocorticoids, as the first-line anti-inflammatory and immunosuppression drug, were used in clinical OLP treatment. Although glucocorticoids provided an extent of symptomatic relief, they were prone to side effects and drug resistance.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that numerous monocytes at the basement membrane of OLP tissue differentiated into M1 macrophages, which intensified inflammation in the lesion area by secreting inflammatory cytokines such as IL-1β, TNF-α. [ 39 ] Mast cell degranulation played an extremely critical role in the OLP’s basement membrane disruption. [ 43 ] Substantial experimental data suggested that helper T cells, including Th1, Th2, Treg, and Th17 subsets, were involved in the pathogenic process of OLP.…”
Section: Discussionmentioning
confidence: 99%
“…However, the causes that initiate and/or perpetuate OLP are still not fully understood, and only a small number of risk factors, such as the immune response, genetic background, infectious agents, stress, and drugs, are currently believed to possibly play a role in OLP pathogenesis 5 . The current literature indicates that immune factors may be key to the pathogenesis of OLP 6,7 . In particular, T‐cells have been shown to be crucial in the development of illness 8 .…”
Section: Introductionmentioning
confidence: 99%
“… 5 The current literature indicates that immune factors may be key to the pathogenesis of OLP. 6 , 7 In particular, T‐cells have been shown to be crucial in the development of illness. 8 In addition, in the early stage of disease development, more apoptotic keratinocytes can be found, 9 indicating that keratinocytes may be target cells in the early stage of disease occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Lichen planus is a common chronic inflammatory mucosal and skin disorder that affects approximately 0.5–4% of the worldwide population, with a malignant transformation rate of 1.4% [ 1 , 2 ]. Also, OLP had a higher prevalence among middle-aged females [ 3 , 4 ], while it is also rare in children (0.03%) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%